Asthma in children. (May 2016) - Chavasse, Richard J.; Kerr, Maya
Abstract: Asthma is a common disorder in children and places a high burden on healthcare resources. Despite the publication of evidence-based guidelines, morbidity and mortality remain unacceptably high. Most children and young people can be managed with relatively straightforward management plans. Consistent implementation of current guidelines with a whole-system approach involving primary, secondary care and community pharmacies is needed to improve outcomes.